Atopy as a Modifier of the Relationships Between Endotoxin Exposure and Symptoms Among Laboratory Animal Workers. Issue 8 (20th July 2017) - Newton, Ashley N; Davis, Meghan; Koehler, Kirsten; Shreffler, Wayne; Ahluwalia, Sharon; Metwali, Nervana; Thorne, Peter S; Paigen, Beverly J; Matsui, Elizabeth C
Abstract: Background: Exposure to endotoxin is known to trigger airway inflammation and symptoms, and atopy may modify the relationship between endotoxin exposure and symptom development. Objective: To test the a priori hypothesis that atopic status modifies the relationship between endotoxin exposure and respiratory symptom development. Methods: A prospective study of laboratory workers at The Jackson Laboratories was conducted. Allergy skin testing was performed and population demographic and clinical information was obtained at baseline. Personal exposure assessments for airborne endotoxin and surveys of self-reported symptoms were performed every 6 months. Cox proportional hazards models were used to examine the relationship between endotoxin exposure and development of mouse-associated symptoms and multivariate regression was used to test for interaction. Results: Overall, 16 (9%) of 174 worker-participants developed mouse-associated rhinoconjunctivitis symptoms by 24 months and 8 (5%) developed mouse-associated lower respiratory symptoms by 24 months. Among workers with endotoxin exposure above the median (≥2.4 EU m −3 ), 5 (6% of 80) atopics reported mouse-associated rhinoconjunctivitis symptoms at 24 months as compared to 3 (3% of 94) non-atopics. Among workers below the median endotoxin exposure (<2.4 EU m −3 ), 1 (1% of 80) atopic reported mouse-associated rhinoconjunctivitis symptoms at 24 months as compared to 7 (7% of 94) non-atopics. For the combination of symptoms, the adjusted hazard ratio was 6.8 (95% confidence interval: 0.7–67.2) for atopics and 0.07 (95% confidence interval: 0.01– 0.5) for non-atopics. Conclusion: In this occupational cohort, atopic workers may be more susceptible to, and non-atopic workers protected from, endotoxin-associated upper and lower respiratory symptoms.